DESIGN STRATEGY OF VOCATIONAL SCHOOL OF FINE ARTS WITH PHSYCOLOGICAL ARCHITECTURE STUDIES - Natasia Anggi Laxmita; Suparno Suparno; Tri Yuni Iswati (ARSITEKTURA, 2019)
Education is a such a priority and its necessary for student to improve their skill to be able to employe themself for a job rivals. Because in this growing era demands more competent students are needed to be considered in the world of work, especially in a fine arts school. This study aims to know how the psychology of architecture applied in the vocational school of fine art. Psychological architecture is a field of study that studies the relationship between built environment and human behavior, which mutually affect one another. The built environment and human behaviour able to develop their own potential, so that the environment will greatly affect the development of student’s potential. This design strategy is located in Klaten. The research method used is applied research, through the data collection which then concluded and become the guidance in the design analysis.  The application of psychological architecture in this building is done through the design in accordance with the user’s characteristics, by connecting the characteristics and theories of psychological architecture. The result of application can be seen in users, activities, site, space, lay out arrangement and also the appearance of interior and exterior. The analysis process that apply psychology of architecture study can give a result of school design which give comfort when the user doing the activity.